METODE DAKWAH PADA MASYARAKAT MULTI ETNIK (Studi pada Da’i di Kanagarian Koto Baru Kecamatan Luhak Nan Duo Kabupaten Pasaman Barat) - Neni Efrita; Rika Tri Apyeni (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Communities in the Kenagarian region of New Koto, Luhak Nan Duo District, West Pasaman Regency have many (diverse) tribes, namely: Javanese, Minang and Mandhailing. The diversity of people with various tribes (multi ethnicity) will certainly demand that a preacher is able to choose the correct method of preaching in its delivery, because this society also has a different level of understanding. The purpose of this study is to find out the method of da'wah wa-hikmah 'Izatil Hasanah and Al-Mujadalah Bi-Al-Lati Hiya Ahsan used by the preacher when preaching to the multicultural community in the Kenagarian Koto Baru District of Luhak Nan Duo Kabubaten, West Pasaman. This research method uses descriptive qualitative methods with data collection techniques used observation, interviews and documentation. The results of the study show that: (1) the wisdom method used in multiethnic societies, generally paying attention to the situation and conditions of the community and paying attention to the ability of mad'u to receive the material conveyed through stories in the Qur'an and Sunnah; (2) hasanah method by giving advice using language that is easy to understand and not infrequently da'i intersperse his preaching with regional languages and material used by da'i in giving good news and bad news; and (3) the mujadalah method is rarely used by da'i because this method is not suitable given to ordinary people.